Picturing the Progressive Education: Images and Propaganda in The New Era (1920-1939) - Braster, Sjaak; Pozo Andres, Maria del Mar (Historia y Memoria de la Educación, 2018)
In this article we analyse the propaganda work done by the journal The New Era for divulgating and popularising the progressive education movement. The review started in 1920, so it was the first in transmitting the ideas of this movement, and also the first English language journal that became the channel of expression of the New Education Fellowship, for divulgating the innovative ideals in the Anglo-saxon countries. We have studied the propaganda work from the images that the journal has published between 1920 and 1939. As a research method we have chosen a combination of content analysis and a grounded theory approach. We have identified a list of categories that are connected with the characteristics of new or progressive education. We have considered as starting point that all the ideals and school practices made more visible by the journal, i.e., the ones that were shown in many images, were those used for building a public image of the New Education. We have organized the visual discourse built by The New Era around six ideas: coeducation, activity, freedom, nature, child-centered, and individualization versus socialization. We have quantified the number of images that were published in connexion with everyone of these ideas, making comparisons between spaces and times. The quantitative analysis has allowed us to explain general patterns and exceptional features. Finally, we present the most remarkable characteristics of the iconographical discourse about the New Education that was built and propagated by The New Era.